Sprostowanie niektórych tłumaczeń z tureckiego ws. Nowy przekład dziejopisów tureckich Ignacego Pietraszewskiego – pomiędzy recenzją a translacją - Klimek-Grądzka, Jolanta (ANNALES UNIVERSITATIS PAEDAGOGICAE CRACOVIENSIS. STUDIA LINGUISTICA, 2018)
Subject to analysis in this article is the genre status of Ignacy Pietraszewski’s works commenting upon Collectanea by Józef Sękowski. The former work by Pietraszewski is a press edition of Sprostowania niektórych tłumaczeń z tureckiego [Corrections of Some Translations from Turkish] (1845), while the latter is an expanded, book edition of Corrections..., entitled Nowy przekład dziejopisów tureckich [A New Translation of Turkish History Writers] (1846). A research question asked in the article is to what extent Pietraszewski’s comments on Sękowski oeuvre is a case of translation or a case of translation criticism. Drawing upon the stylistic features of both works by Pietraszewski, their evaluative and judgmental lexis and their dialogical nature, the author decided that these works are critical reviews of Sękowski’s Collectanea. The reviews display an ostesibly marked polemical aspect. They contain evaluation of the target text and they mark a breach of the text-type canon by incorporating a didactic component.